A Literature Review: Efforts to Overcome Student’s Mathematical Literacy - Mohammad Nurwahid; Sofia Ashar (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Mathematics is closely related to everyday life, by using mathematics we can solve problems of everyday life related to mathematics. The purpose of learning mathematics and mathematical abilities is contained in mathematical literacy. Mathematical literacy is a person's ability to formulate, use and interpret mathematics in a variety of contexts. Therefore, mathematical literacy must be mastered by students. However, in reality the mathematical literacy of Indonesian students is still low. The method used in this research is literature study. The data collected is in the form of research results from various articles, library sources and documents that are in accordance with the theme of the factors causing the low mathematical literacy skills of Indonesian students and efforts to improve them. The results of this study are the low mathematical literacy is caused by several factors including the learning process is still much teacher-centered, the lack of students practicing literacy questions, students have difficulty making mathematical models from real-world problems. These problems must be addressed immediately. The solution offered in this paper is to use contextual learning because literacy is closely related to the real world context, improve mathematical thinking habits, and get students to practice literacy questions or PISA-type questions. This solution is expected to improve students' mathematical literacy skills.